Left-hand techniques in piano playing: an analysis of performance of Scriabin's prelude Op. 9 no. 1 by Yuja Wang / Miera Liyana Abdul Rahman - Abdul Rahman, Miera Liyana (2022)
The nature of playing piano is always played with two hands and the main melody is usually located on the right-hand. While the right-hand often has the theme material, the left-hand is often paid less attention to. Left hand is a very crucial part for pianist. It often got mistaken for not being the important part in piano performance. Both hands are equally important in piano playing. The objectives of this study are to investigate the use of left-hand technique in piano playing and to study the performance of Prelude Op. 9 No. 1 for the Left-Hand, Alexander Scriabin by Yuja Wang. This study will be focusing on a left-hand alone piece by Alexander Scriabin. This piece shows great example of using the proper left-hand technique. It is better to develop our left-hand techniques by observing a left-hand alone music because we can address the specific technical problems that is associated with left-hand piano music.